Assistência estudantil no ensino superior: uma análise do Programa Auxílio Estudantil da Universidade Tecnológica Federal do Paraná, Campus Toledo. - Senger, Amália (2018)
With the anlargement of the social and economic condicions gestated by capitalist Society, actions are taken for democratize the higher education and decreasing the avoidance of public higher education. In this understanding, there is student assistance, in the perspective to expand the conditions of the student's stay in higher education, faced with the difficulties experienced by the working class. Thus, the present study has as object the Student Aid Program (PAE), of the technological university of Paraná (UTFPR), Campus Toledo, problematizing the extent to which this program has achieved its intended purpose, to support students from families with a per capita income of up to a minimum wage and a half, in what refers to the permanence in the institution so that they do not give up because of socioeconomic difficulties? The general objective of this dissertation is to analyze if the Student Aid Program is effective in supporting the permanence of UTFPR students, Toledo campus. To understand the object, to base the research and to answer the proposed objective, the study perpasses by the categories: student assistance, education, social politic, higher education, work, capital and state. These categories are related, since student assistance, present in federal public higher education, interact directly with the student conditions that are presented in education, characterized as social policy, offered by the State, which has its development directly related to work and, at present, is at the service of capital. In the search for an understanding of the relations between the categories, methodologically, quantitative and qualitative data were used in the research, from the PAE edicts, of the entire enrollment and selection process, of the data of the academic system, in the interview that the Nucleus of Psycho-pedagogical Monitoring and Student Assistance with students who give up/lock the course, and the field research carried out with the students selected by the program in question. With the analysis of the data collected by the research, it was possible to identify that the “PAE’’ is relevant for the students' stay in the institution, supporting it to dedicate themselves to the studies, both economically and psychologically, although the program does not bear all relevant expenses to academic life. Despite the limits imposed, such as selectivity, expressive demand and the waiting list, the research revealed that student assistance, more specifically the PAE, is fundamental for the realization of the student’s right to stay in the institution, given the contradictions generated by capitalist society.